Future projection of summer surface air temperature trend over central India: Role of external forcing and internal variability. (18th September 2019) - Nath, Reshmita; Luo, Yong; Chen, Wen
Abstract: This study investigates the relative contribution of internal variability and external forcings on summer (June–August) surface air temperature (SAT) over the central Indian landmass. Here we use Community Earth System Model Large Ensemble (CESM‐LE) data to assess the historical (1966–2005) and future (2010–2060) climate change in presence of internal climate variability. The summer SAT trend during the historical period exhibits an amplified cooling (<−3°C), whereas a warming trend (≥4°C) is projected in all the ensemble members under RCP8.5 scenario. The total trend is then partitioned into contributions from the externally forced response and internal climatic variability. Over the Indian region, the external forcing displays a strong cooling trend during the historical period and warming trend under RCP8.5 scenario. On the other hand, natural variability displays mainly cooling trends and it introduces a wide range of uncertainty to the future projection in climate models. In historical period, the signal‐to‐noise ratio (SNR), that is, ratio of external forcings and internal variability, is less than 1, which indicates that the internal climatic variability dominates over the forced response. But in future decades the SNR is much higher than 1, that is, external forcing overrides the internal variability. However, to a greater extent natural variability will mask the warming trend over the Indian region, even under RCP8.5 scenario. Abstract : Relative contribution of external forcing factors and internal variability on summer surface air temperature trends over central India are investigated here. CESM multi‐model ensembles are used to assess the historical and future climate change in presence of internal variability. In historical period, internal variability dominates over external forcings, but in future external forcings will override the internal variability. The internal variability no longer will mask the warming trend due to external forcing factors under RCP8.5 scenario.